A clathrin mediated endocytosis scaffolding protein, Intersectin 1, changes in an isoform, brain region, and sex specific manner in Alzheimer’s disease - Jaye, Sierra; Sandau, Ursula S.; McFarland, Trevor J.; Woltjer, Randy L.; Saugstad, Julie A. (Frontiers in Neuroscience, 2024)
Alzheimer’s disease (AD) is the most common form of dementia and is characterized by the accumulation of amyloid-beta (Aβ) plaques and neurofibrillary Tau tangles in the brain. We previously identified a set of candidate AD microRNAs (miRNAs) in human cerebrospinal fluid (CSF) and used a target prediction pipeline to identify mRNAs and pathways that could potentially be regulated by the miRNAs. Of these pathways, clathrin mediated endocytosis (CME) was selected for further investigation. CME is altered in multiple brain cell types in AD and is implicated in early cellular phenotypes such as enlarged early endosomes and pathogenic processing of Aβ. However, a comprehensive evaluation of major CME hub proteins in humans with AD across multiple brain regions is lacking. Thus, we used immunoblots to evaluate human post-mortem AD and control (CTL) frontal cortex (FC; AD n = 22, CTL n = 23) and hippocampus (HP; AD n = 34, CTL n = 22) for changes in Intersectin 1 (ITSN1), Phosphatidylinositol Binding Clathrin Assembly Protein gene (PICALM), Clathrin Light Chain (CLT), FCH and Mu Domain Containing Endocytic Adaptor 1 (FCHO1), Adaptor Related Protein Complex 2 (AP2) Subunit Alpha 1 (AP2A1), and Dynamin 2 (DNM2). Of these, we found that in AD, ITSN1-long (ITSN1-L) was decreased in the FC of males and HP of females, while ITSN1-short was increased in the HP of both males and females. We further evaluated ITSN1-L levels in cortex (CTX) and HP of the 5xFAD mouse model of Aβ pathology at different timepoints during aging and disease progression by immunoblot (n = 5–8 per group). At 3 months, female 5xFAD exhibited an increase of ITSN1-L in CTX but a decrease at 6 and 9 months. Additionally, immunofluorescent staining of 5xFAD primary HP neurons showed an increase of ITSN1-L in matured 5xFAD neurons at 21 and 28 days in vitro. Together, our studies show that in AD, isoforms of ITSN1 change in a brain region-and sex-dependent manner. Further, changes in ITSN1-L are transient with levels increasing during early Aβ accumulation and decreasing during later progression. These findings suggest that ITSN1 expression, and consequently CME activity, may change depending on the stage of disease progression.